Angela Merkel’s last term: an introduction - Zohlnhöfer, Reimut; Engler, Fabian (German politics, 2024)
This introduction to the special issue first describes the cumbersome process of forming the fourth and final Merkel government. Both coalition partners experienced severe electoral losses in 2017 and were not particularly close to one another programmatically. This made the formation of a new coalition difficult. Next, the to-do-list is discussed. It turns out that, as a response to the Fridays-for-Future protests, voters considered climate change to be the most important problem in 2019, while the Corona pandemic dominated the agenda from early 2020. Interestingly, none of the coalition parties ‘owned’ either of these issues and this could have made policy-making even more intricate. In the third part, we summarise the policy profile of the fourth Merkel government, based mostly on the contributions to this special issue. It turns out that the policies of the fourth Merkel government mirrored those of its predecessor. In the socio-economic dimension a gentle de-liberalisation continued, while the policies on the social dimension followed a moderately liberal path. In the final section, the plan of the special issue is outlined.